Saint Mamas at Exeles: An Unusual Case of Ritual Piety on Karpathos - Angeliki Katsioti; Nikolaos Mastrochristos (Arts, 2023)
The church of Saint Mamas is a small, domed structure that lies close to Menetes village in Karpathos. It preserves most of its painted decoration, consisting of the scene of the Ascension of Christ on the dome and saintly figures on the rest of the surfaces. A dedicatory inscription, read here for the first time, dates the frescoes to 1312/3 and places them in the broader context of precisely dated monuments. Certain features of the iconographic program, such as the presence of healer saints (Panteleemon and Kyprianos) but mostly of the officiating Pope Sylvester and the passage used in the codex of Christ Pantocrator on the apse of the altar, lead us to interesting conclusions concerning, among other things, the perception of anti-Latin propaganda in the islands of the South Aegean. Also, the stylistic affinities between the art of Karpathos and Crete corroborate the diachronic interrelations between the two islands. The church of Saint Mamas is an exceptional example and one of the few Byzantine-decorated monuments that survive on the island.